Pain and Disability: Indirect Assessment of Quality of Life Using the WHODAS 2.0 Scale in Patients with Chronic Pain - Asanova Азізе (Psychosomatic Medicine and General Practice, 2025)
Background. Chronic pain is not merely a physical symptom, but a complex phenomenon that affects all aspects of a person’s life. It impacts physical health, psycho-emotional well-being, social relationships, and professional functioning. Chronic pain significantly diminishes quality of life, often leading to both functional and psychological disability. There is an increasing need for objective measurement of how chronic pain influences functioning across different life domains. The WHODAS 2.0 provides both quantitative and qualitative insights into impaired functioning, serving as a crucial tool in the development of personalized treatment strategies. This is particularly relevant for multidisciplinary teams managing patients with chronic pain. Materials and methods. The study involved 147 adult outpatients aged 18 to 70 years diagnosed with primary, secondary, or mixed chronic pain lasting more than three months, in accordance with ICD-11 criteria. Socio-demographic information and pain-related clinical characteristics were collected using a structured screening questionnaire. Psychological factors, including anxiety and depression, were assessed using the Hospital Anxiety and Depression Scale (HADS). The WHODAS 2.0 tool was employed to evaluate functional impairment and to indirectly assess pain-related quality of life. Data were processed and analyzed using MS Excel and Jamovi software on the Windows 11 platform, applying standard methods of statistical analysis. Results. The majority of participants reported difficulties on the WHODAS 2.0 scale in the domains of «Life Activities» and «Participation in Society» (56.6% and 54.5%, respectively), although the levels of dysfunction were generally mild to moderate. Statistically significant gender differences were observed in the domains of «Understanding and Communicating», «Getting Around», and «Life Activities». Dysfunction scores on the WHODAS 2.0 scale were significantly associated with both financial status and the number of pain locations. Participants experiencing pain in more than two locations demonstrated higher levels of dysfunction compared to those with pain confined to a single area (W = 5.03, p = 0.001). Correlation analysis revealed significant positive associations between dysfunction and all assessed variables: depression (rs = 0.647, p < .001), anxiety (rs = 0.618, p < .001), and pain intensity (rs = 0.379, p < .001), with the strongest correlation observed between depression and functional impairment. Group comparisons showed that participants who were physically inactive had significantly higher mean dysfunction scores (M = 73.4, SD = 27.1) than those who engaged in physical activity (M = 62.8, SD = 19.8), with a mean difference of 7 points (U = 2035, p = 0.022). Similarly, participants with sleep disturbances reported higher dysfunction scores (M = 72.8, SD = 26.0) compared to those without sleep issues (M = 60.5, SD = 19.0), with a mean difference of 9 points (U = 1654, p = 0.003). Pain intensity was significantly associated with financial status (χ² = 7.31, df = 2, p = 0.026), employment status (χ² = 8.32, df = 2, p = 0.016), and number of pain locations (χ² = 9.00, df = 2, p = 0.011). Participants with lower income, unemployment, and pain in multiple locations reported higher levels of both pain and functional impairment. Conclusions. Chronic pain substantially affects both the physical and mental health of patients. Its impact is not limited to pain characteristics alone, but is also strongly associated with psycho-emotional and social factors such as anxiety, depression, sleep disturbances, physical inactivity, and financial hardship. The WHODAS 2.0 scale serves as an effective instrument for comprehensive assessment of disability, enabling a deeper understanding of patients’ needs and supporting the development of personalized, multimodal treatment strategies. Materials and methods. The study included 147 adult outpatients aged 18 to 70 years with a diagnosis of primary, secondary or mixed chronic pain lasting more than three months according to ICD-11 criteria. Socio-demographic data and clinical characteristics related to pain were collected using a screening questionnaire, psychological factors, such as anxiety and depression, were assessed using the HADS scale. The WHODAS 2.0 scale was used to assess dysfunction and indirectly assess the quality of life associated with chronic pain. Data preparation and analysis were performed in MS Excel and Jamovi software on the Windows 11 platform using mathematical statistics methods. Results. The majority of participants reported difficulties on the WHODAS 2.0 scale in the domains related to «Life activities» and «Participation in society» (56.6% and 54.5%), but the levels of dysfunction were mild to moderate. Differences were found between men and women in the domains of «Understanding and Communicating», «Getting around» and «Life Activities». The level of dysfunction on the WHODAS 2.0 scale significantly depends on financial status and the number of pain locations. Patients with pain in more than two locations have a higher level of dysfunction compared to those with pain in only one area (W = 5.03, p = 0.001). Correlation analysis showed that the level of dysfunction on the WHODAS 2.0 scale had significant positive correlations with all the variables studied: depression (rs = 0.647, p < .001), anxiety (rs = 0.618, p < .001) and pain intensity (rs = 0.379, p < .001). The strongest correlation was observed between depression and the level of dysfunction. Statistically significant differences were found between groups (U = 2035, p = 0.022), where participants who did not engage in physical activity had a higher mean level of dysfunction (M = 73.4, SD = 27.1) compared to those who did engage in physical activity (M = 62.8, SD = 19.8). The mean difference between the groups was 7 points. Differences were also present between the groups of participants with and without sleep disturbances (U = 1654, p = 0.003). Participants with sleep disturbances had a higher level of dysfunction on the WHODAS 2.0 (M = 72.8, SD = 26.0) compared to those without sleep disorders (M = 60.5, SD = 19.0). The mean difference between the groups was 9 points. Pain intensity was significantly associated with financial status (χ² = 7.31, df = 2, p = 0.026), employment (χ² = 8.32, df = 2, p = 0.016), and number of pain locations (χ² = 9.00, df = 2, p = 0.011). Participants with lower financial status, unemployed, with chronic pain in more than two locations had higher levels of pain and dysfunction. Conclusions. Chronic pain has a significant impact on patients physical and mental health and is associated not only with pain characteristics, but also with psycho-emotional and social factors such as anxiety, depression, sleep disturbances, physical inactivity and financial difficulties. The WHODAS 2.0 scale is an effective tool for a comprehensive assessment of dysfunction, which allows for a better understanding of patients’ needs and the development of personalised multimodal treatment strategies.